A reinvenção da educação de jovens e adultos pelos professores e alunos: uma pesquisa sociopoética - Soares, Rosileide Maria Silva (2009)
Since its begging, the Education of Youth and Adults (EYA) had a tendency to be guided by the paradigms of diagnosis and prescription, which emphasize the concept of need and idealization. The latter considers the “should be” as the ideal to be achieved thereby not focussing on the concrete practices of this educational method. That is why I asked myself the following question: to what extent can one produce EYA concepts that are beyond diagnosis and prescription? Such an issue made me see the sociopoetics as the most appropriate research method to investigate this topic since it is a philosophical practice whose aim is to help the target group to produce confetos (concept plus affection) about the topics it focuses on. So as to achieve that, it transforms the target group into co-researchers, using a variety of languages that enhance the ability of the “whole body” to produce knowledge and allows the field research to occur as workshops. In my research, I used three groups to address that issue, two of which being composed of teachers and one of students. The teachers and students belong to two public schools in Fortaleza that provide education for youth and adults. I used several techniques which dealt with several languages. Through them, the co-researchers related the EYA to the following items: food, drink, myth, dance, music, weapon and embroidery. In addition, they related EYA to the subtopic of my creations in EYA. The main results found about EYA are more related to the action, diversity and difference than the concepts of diagnosis and prescription present in their official conceptions. What brought me to that conclusion were mainly the confetos (concept plus affection) of EYA-infinite diversity, EYA-embroidery, EYA-mask and EYA-improving, EYA-vital energy, EYA-empty, EYA-world-wandering, EYA-motor-perceptor and EYA-calm down, EYA-transgression, student-transgressor, student-devourer, student-dolls of different colors, EYA-pain in the neck’ book, staircase- teachers, EYA-mandala and my creations in EYA-question that led me to such conclusions.